Determinant of Customer Decisions in Choosing The Savings Products at Bank Riyal Irsyadi - Muhammad Nur Khairil Anwar; Azid Syuk Roni; Rahmi Kusuma Dewi (UIN Siber Syekh Nurjati Cirebon, 2024)
Abstract The purpose of this study is to find out the factors that influence customers in choosing the Riyal Irsyadi Bekasi Islamic bank. The respondents in this study were 100 people with the provision of Sharia bank savings user Riyal Irsyadi as a sample and the place of the research conducted in the city of Bekasi. The research method uses descriptive quantitative with purposive sampling techniques. The results of this study show that the factors of religiosity, social, and marketing promotion. It is evidenced by the results of the percentage of questionnaires distributed to the sample with a value of 58% of the variables studied, 42% of the variables that were not studied where other factors were outside the variables that had been studied. Based on the results of multiple linear regression analysis, it can be stated that of the three variables studied, it turns out that the service factor variable is 143.214 which has a more dominant coefficient value than other factor variables. The second high coefficient value is the social environment with a value of 1.054 then the lowest coefficient value is the religiosity variable 0.357 It can be concluded from the results of the research that the biggest factor that influences customers to choose Riyal Irsyadi Sharia Bank savings is the service factor where Islamic bank products have excellent service, have products needed by customers, as well as the existence of offers with Islamic principles without usury, garar, and maysir, all of which include aspects of the principles of the Riyal Irsyadi's Islamic bank. Keywords: Islamic Bank, Customer Service, Savings product. AbstrakTujuan penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi nasabah dalam memilih bank syariah Riyal Irsyadi bekasi. Responden dalam penelitian ini berjumlah 100 orang dengan ketentuan nasabah tabungan bank syariah Riyal Irsyadi sebagai sampel dan tempat penelitian dilakukan di kota bekasi. Metode penelitian menggunakan deskriptif kuantitatif dengan teknik purposive sampling. Hasil penelitian ini menunjukkan bahwa faktor religiusitas, sosial, dan promosi pemasaran. Dibuktikan dengan hasil presentase kuesioner yang disebarkan kepada sampel dengan nilai sebesar 58% variabel yang diteliti, 42% variabel yang tidak diteliti dimana faktor lainnya berada diluar variabel yang telah diteliti. Berdasarkan hasil analisis regresi linier berganda dapat dinyatakan bahwa dari ketiga variabel yang diteliti ternyata variabel faktor pelayanan sebesar 143,214 memiliki nilai koefisien yang lebih dominan dibandingkan variabel faktor lainnya. Nilai koefisien tinggi kedua yaitu variabel lingkungan sosial dengan nilai sebesar 1,054 kemudian nilai koefisien terendah yaitu variabel religiusitas 0,357. Dari hasil penelitian dapat disimpulkan bahwa faktor terbesar yang mempengaruhi nasabah memilih tabungan Bank Syariah Riyal Irsyadi adalah faktor pelayanan dimana produk bank syariah memiliki pelayanan yang sangat baik, memiliki produk yang dibutuhkan oleh nasabah, serta adanya penawaran dengan prinsip syariah tanpa riba, garar, dan maysir yang kesemuanya itu sudah termasuk aspek prinsip bank syariah Riyal Irsyadi.Kata Kunci : Bank Syariah Riyal Irsyadi, Nasabah, Keputusan Memilih Produk.